Narrative identity differences in autism - Mélissa C. Allé; Priscille Schneider; Lyla Rigoulot; Marie-Charlotte Gandolphe; Jean-Marie Danion; Romain Coutelle; Fabrice Berna (Scientific Reports)
Abstract Autism is characterized by a modification of the sense of self, particularly self-continuity. While former studies focused on the recollection and narrative of single past events, the present study aimed to explore autistic individuals’ narrative identity by assessing for the first time their life story, described as the most integrated form of personal narrative and the closest to the self. A comparison of the narrative coherence of autistic individuals’ life stories (n = 22) with those of nonautistic participants (n = 22) revealed that global coherence, particularly causal-motivational coherence, was lower in the life narratives of autistic individuals. Additionally, typical narrative beginnings at birth and elaborated endings were less frequent in autistic individuals. In comparison with the nonautistic group, the autism group included personal events in their life narratives that were self-rated as more negative and associated with negative feelings at retrieval, along with having lower life impacts. The present study provides evidence for a different narrative identity in autism. We discussed how this effect could be related to variations in narrative coherence and temporal framework, possibly influenced by differences in others’ perspective-taking.